Investigation of Shade Tree Species Used in Tea Garden in Bangladesh (SAARC Journal of Agriculture, 2020)
The shade trees are an integral component of tea cultivation in Bangladesh. The shade trees are essential for modulating the environment of the tea ecosystem, enriching the soil fertility, reducing temperature and the evaporative capacity, conserve soil moisture and helps in the control of certain pests and diseases which are positively thermotropic in nature. The shade trees provide partial shade to the tea plants, which is important for improving the quality of the tea leaf. The right type of shade trees and their proper management is a prerequisite for successful tea crop growing. For this persists, a floristic exploration of shade trees was carried out at fifteen tea gardens in Chattogram and Moulvibazar District of Bangladesh from November 2017 to December 2018. During the investigation, a total of 44 species of Angiosperm representing 31 genera of 9 families was enlisted. For every species, scientific name, vernacular name, status, and necessary photographs are mentioned. In the assessment, the Fabaceae family shows the highest number of shade trees comprising 19 genera and 31 species. The most common permanent shade tree species among the tea gardens are Albizia odoratissima, A. chinensis, A. lebbeck, A. lucidior, A. procera, and Derris robusta. Indigofera teysmannii is frequently using as a temporary shade species in all investigated tea gardens. Cajanus cajan, Tephrosia candida, Tephrosia candida, Gliricidia sepium, Erythrina lithosperma and Desmodium gyroides species are also used as temporary shade trees in many tea gardens. Further investigations, however,are required to find out the right type of shade tree species on the growth and yield of tea plants in tea cultivation areas of Bangladesh.SAARC J. Agri., 18(1): 219-237 (2020)